PLCγ-dependent mTOR signalling controls IL-7-mediated early B cell development. Issue 1 (December 2017) - Yu, Mei; Chen, Yuhong; Zeng, Hu; Zheng, Yongwei; Fu, Guoping; Zhu, Wen; Broeckel, Ulrich; Aggarwal, Praful; Turner, Amy; Neale, Geoffrey; Guy, Cliff; Zhu, Nan; et al.
Abstract The precise molecular mechanism underlying the regulation of early B cell lymphopoiesis is unclear. The PLCγ signaling pathway is critical for antigen receptor-mediated lymphocyte activation, but its function in cytokine signaling is unknown. Here we show that PLCγ1/PLCγ2 double deficiency in mice blocks early B cell development at the pre-pro-B cell stage and renders B cell progenitors unresponsive to IL-7. PLCγ pathway inhibition blocks IL-7-induced activation of mTOR, but not Stat5. The PLCγ pathway activates mTOR through the DAG/PKC signaling branch, independent of the conventional Akt/TSC/Rheb signaling axis. Inhibition of PLCγ/PKC-induced mTOR activation impairs IL-7-mediated B cell development. PLCγ1/PLCγ2 double-deficient B cell progenitors have reduced expression of genes related to B cell lineage, IL-7 signaling, and cell cycle. Thus, IL-7 receptor controls early B lymphopoiesis through activation of mTOR via PLCγ/DAG/PKC signaling, not via Akt/Rheb signaling. IL-7R activation drives early B cell development, but the signalling is unclear. Here the authors show PLCγ is involved in IL-7R-induced mTOR activation via a DAG/PKC-dependent pathway, and that double deficiency of the two PLCγ isoforms arrests B cell development at the pre-pro-B stage in mice.